Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858101
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation on Online Learning Approaches using Parallel Coordinate Visualization

Abstract: As visualizations are increasingly used as a storytelling medium for the general public, it becomes important to help people learn how to understand visualizations. Prior studies indicate that interactive multimedia learning environments can increase the effectiveness of learning [11]. To investigate the efficacy of the multimedia learning environments for data visualization education, we compared four online learning approaches-1) baseline (i.e., no tutorial), 2) static tutorial, 3) video tutorial, and 4) int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…By studying whether the ideas of active reading of text might be applicable to the reading of visualizations, we open the door to the possible benefits of applying ideas from the extensive active reading research to challenges in reading visualizations, such as visualization literacy [12,38,40]. Starting with a qualitative study, we observed the actions people employed to read visualizations.…”
Section: Introductionmentioning
confidence: 99%
“…By studying whether the ideas of active reading of text might be applicable to the reading of visualizations, we open the door to the possible benefits of applying ideas from the extensive active reading research to challenges in reading visualizations, such as visualization literacy [12,38,40]. Starting with a qualitative study, we observed the actions people employed to read visualizations.…”
Section: Introductionmentioning
confidence: 99%
“…Six participants reported that playing with configurable parameters of recommendations (e.g., re-sizing points by a slider bar in Figure 4) in addition to using the three representation methods helped them understand the recommendations (i.e., learning-bydoing [KL16]). For example, P10 PTAT said he better understand Change Point Opacity when he adjusted the level of opacity using the slider bar ( Figure 4D): "[The] difference [between the specified view and Preview for Change Point Opacity] was subtle, but I understood [Change Point Opacity] by adjusting it."…”
Section: Learning By Doingmentioning
confidence: 99%
“…The learning-by-doing approach [KL16], which is known to be useful for learning parallel coordinate plots, was also useful for understanding the behavior of recommendations during the visual construction process. Therefore, we believe visualization recommendation interfaces must support the learning-by-doing approach by giving users the opportunity to play with recommendations.…”
Section: Support Learning By Doingmentioning
confidence: 99%
“…The visualization community recognizes this and is taking steps to improve visualization literacy within the general public. Recent efforts to improve visualization literacy investigate how instructional materials should be designed [18,20,36,37]. Ruchikachorn and Mueller demonstrated that by morphing visualizations from the familiar to the unfamiliar, participants could learn new representational forms [18].…”
Section: Visualization Literacymentioning
confidence: 99%
“…Kwon and Lee further studied active learning strategies. Using the parallel coordinates visualization and three tutorials types: static, video, and interactive, they observed that participants with the interactive and video tutorials outperformed participants with static or no tutorials [36]. Some of the studies mentioned above have focused on simple visualizations, while others have investigated visualization literacy for static visualizations.…”
Section: Visualization Literacymentioning
confidence: 99%